Aesop's fables - Aesop ([S.l.] : CreateSpace Independent Publishing Platform, 2014)
Aesop's Fables or the Aesopica is a collection of fables credited to Aesop, a slave and story-teller believed to have lived in ancient Greece between 620 and 560 BCE. Of diverse origins, the stories associated with Aesop's name have descended to modern times through a number of sources. They continue to be reinterpreted in different verbal registers and in popular as well as artistic mediums.